Nascent Adhesion Clustering: Integrin-Integrin and Integrin-Substrate Interactions - Kuanpo Lin; Robert J. Asaro (Biophysica, 2022)
Nascent adhesions (NAs) are a general precursor to the formation of focal adhesions (FAs) that provide a fundamental mechanism for cell adhesion that is, in turn, involved in cell proliferation, migration, and mechanotransduction. Nascent adhesions form when cells come into contact with substrates at all rigidities and generally involve the clustering of ligated integrins that may recruit un-ligated integrins. Nascent adhesions tend to take on characteristic sizes in the range of <semantics>O(100<mspace width="3.33333pt"></mspace>nm–150<mspace width="3.33333pt"></mspace>nm)</semantics> in diameter and tend to contain integrin numbers of <semantics>O(∼20–60)</semantics>. The flexible, adaptable model we present provides and clear explanation of how these conserved cluster features come about. Our model is based on the interaction among ligated and un-ligated integrins that arise due to deformations that are induced in the cell membrane-cell glycocalyx and substrate system due to integrin activation and ligation. This model produces a clearly based interaction potential, and from it an explicit interaction force among integrins, that our stochastic diffusion-interaction simulations then show will produce nascent clusters with experimentally observed characteristics. Our simulations reveal effects of various key parameters related to integrin activation and ligation as well as some unexpected and previously unappreciated effects of parameters including integrin mobility and substrate rigidity. Moreover, the model’s structure is such that refinements are readily incorporated and specific suggestions are made as to what is required for further progress in understanding nascent clustering and the development of mature focal adhesions in a truly predictive manner.